Economic and environmental analysis to evaluate the potential value of co-optima diesel bioblendstocks to petroleum refiners. (1st February 2023) - Jiang, Yuan; Zaimes, George G.; Li, Shuyun; Hawkins, Troy R.; Singh, Avantika; Carlson, Nicholas; Talmadge, Michael; Gaspar, Daniel J.; Ramirez-Corredores, M.M.; Beck, Andrew W.; Young, Ben; Sittler, Lauren; et al.
Highlights: Developed new refinery analysis approach to simultaneously track economic and environmental benefits. Evaluated 7 diesel-range bio-blendstocks at 3 blending levels, 3 refinery configurations and fuel demand projections over period 2040 to 2050. Sulfur content and cetane number are the primary properties of bio-blendstocks bring value to petroleum refinery. Up to 40% reduction in cradle-to-gate refinery GHG emission is possible when using bio-blendstocks. Abstract: The U.S. petroleum refining sector is undergoing a period of historic transformation, catalyzed by the decarbonization of the U.S. economy. Diesel-boiling-range bioblendstocks have gained traction, owing to their superior fuel properties and environmental performance as compared to traditional petroleum fuels. This work couples refinery linear programming models with life cycle assessment to quantify the potential economic and environmental benefits, and trade-offs, of blending diesel-boiling-range bioblendstocks at petroleum refineries. Linear programming models were developed in Aspen Process Industry Modeling Systems (PIMS) for three representative petroleum refinery configurations of differing complexity. Seven diesel-boiling-range bioblendstocks: 4-butoxyheptane, 5-ethyl-4-propylnonane, soy biodiesel, sludge hydrothermal liquefaction diesel, polyoxymethylene ethers, renewable diesel, and hexyl hexanoate, were investigated to identify key fuel properties that influence refineries' economics and to track the effect of adding bioblendstocks on refinery-wide cradle-to-gate greenhouse gases (GHG) emissions. These analyses considered blending levels from 10 to 30 vol% and fuel demand projections over the period 2040 to 2050. This analysis determines that bioblendstock sulfur content and cetane number are the primary fuel attributes with the potential to provide value to refiners. Life cycle assessment results indicate that the use of diesel-boiling-range bioblendstocks can reduce cradle-to-gate refinery GHG emissions by up to ∼ 40 % relative to conventional refinery operations when considering carbon uptake in the supply chain of the bioblendstock. Refinery-wide marginal GHG abatement costs range from 120 to 3, 600 USD2016/metric tons carbon dioxide equivalent avoided across the scenarios evaluated. Reducing the price of bioblendstocks is identified as a key to their adoption.